2022
DOI: 10.1200/jco.2022.40.4_suppl.310
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled, multicenter study of nab-paclitaxel plus cisplatin followed by surgery versus surgery alone for locally advanced esophageal squamous cell carcinoma (ESCC).

Abstract: 310 Background: Taxane is one of the commonly used chemotherapy drugs for ESCC. Nab-paclitaxel, a small particle albumin-bound form of paclitaxel, showed potentially efficacy in metastatic ESCC. This randomized, controlled, multi-center study is conducted to evaluate the efficacy and safety of nab-paclitaxel plus cisplatin in neoadjuvant treatment of ESCC. Methods: Two hundred and two patients with resectable locally advanced ESCC which was located in the middle or lower third of the esophagus were enrolled a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…A meta-analysis by being said, this result is consistent with our conclusion that the pCR rate in the NCRT group was higher than that in the NICT group, while there were no significant differences in terms of R0 rate. A randomized controlled multicenter study conducted by Liu et al (106) in 2022 reported that patients receiving NCT experienced a pCR rate of 20.8% and an mPR rate of 33.3%, consistent with our findings that the NCT group had the lowest pCR and mPR rates among the all four neoadjuvant treatments.…”
Section: Discussionsupporting
confidence: 92%
“…A meta-analysis by being said, this result is consistent with our conclusion that the pCR rate in the NCRT group was higher than that in the NICT group, while there were no significant differences in terms of R0 rate. A randomized controlled multicenter study conducted by Liu et al (106) in 2022 reported that patients receiving NCT experienced a pCR rate of 20.8% and an mPR rate of 33.3%, consistent with our findings that the NCT group had the lowest pCR and mPR rates among the all four neoadjuvant treatments.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the MPR, latest data from clinical trials presented a 33.3% MPR rate for NCT, 52 whereas the pooled MPR rate for neoadjuvant immunotherapy reached 48.9% in 17 trials, 23,25,27,30,[33][34][35][36][37][38][39][40][41][42][43]46,47 and the highest MPR rate was 72.4% in a study by Shang et al 33 Such outcomes could provide sufficient evidence for the feasibility of neoadjuvant immunotherapy.…”
Section: Discussionmentioning
confidence: 96%
“…Regarding the MPR, latest data from clinical trials presented a 33.3% MPR rate for NCT, 52 whereas the pooled MPR rate for neoadjuvant immunotherapy reached 48.9% in 17 trials, 23 , 25 , 27 , 30 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 46 , 47 and the highest MPR rate was 72.4% in a study by Shang et al 33 Such outcomes could provide sufficient evidence for the feasibility of neoadjuvant immunotherapy. However, because most of the included clinical trials have not revealed long-term follow-up results and complete survival data, we could not ascertain the benefit of neoadjuvant immunotherapy for extended survival.…”
Section: Discussionmentioning
confidence: 99%